Preparation of Free-Standing GaN Substrates from Thick GaN Layers Crystallized by Hydride Vapor Phase Epitaxy on Ammonothermally Grown GaN Seeds - Sochacki, Tomasz; Bryan, Zachary; Amilusik, Mikolaj; Collazo, Ramon; Lucznik, Boleslaw; Weyher, Jan L; Nowak, Grzegorz; Sadovyi, Bogdan; Kamler, Grzegorz; Kucharski, Robert; Zajac, Marcin; Doradzinski, Roman; et al. (Applied physics express, 2013)
Crystallization of GaN by hydride vapor phase epitaxy (HVPE) on ammonothermally grown GaN seed crystals is described. The initial growth conditions for HVPE are determined and applied for further bulk growth. Smooth GaN layers up to 1.1 mm thick and of excellent crystalline quality, without cracks, and with low dislocation density are obtained. Preparation of the free-standing HVPE-GaN crystal by slicing and structural and optical quality of the resulting wafer are presented.